Analisis Implementasi Keputusan Direktur Jenderal Bimas Islam Nomor 379 Tahun 2018 Tentang Bimbingan Pranikah Di Kantor Urusan Agama Kecamatan Sangkapura - Halim, Abdul; Zaki, Zainul (CENDEKIA: Jurnal Studi Keislaman, 2023)
In the Decree of the Director General of Islamic Guidance Number 379 of 2018 concerning instructions for implementing pre-marital marriage guidance for prospective brides and grooms, it is emphasized that this guidance is a real seriousness from the government in creating a strong and harmonious family so as to produce happiness for the prospective bride and groom. This decision is also implemented simultaneously in all provinces of Indonesia, implemented by the district or city Ministry of Religion, District Religious Affairs Office (KUA) or other institutions. The discussion in this research is pre-marital guidance at the Sangkapura District Religious Affairs Office, broken down into 2 research focuses, namely: (1) How is the implementation of pre-marital guidance for prospective brides and grooms at the Sangkapura District KUA? 2) What are the obstacles in implementing the Decree of the Director General of Islamic Community Guidance Number 379 of 2018 in the KUA of Sangkapura District? The research objectives are (1) to determine the implementation of pre-marital guidance for prospective brides and grooms in the KUA of Sangkapura District. (2) mention what are the obstacles in implementing the Decree of the Director General of Islamic Community Guidance Number 379 of 2018 in the KUA of Sangkapura District. The research method uses an empirically based qualitative approach. Data collection uses interview, observation and documentation methods. Data is analyzed by organizing the data, arranging it into patterns, choosing what is important to examine, and making conclusions. Data validation uses observation extension, increased persistence, and triangulation. The results of this research show that: (1) Premarital guidance at the KUA Sangkapura District consists of two guidance models, namely (a) face-to-face guidance by bringing in speakers from the Gresik Ministry of Religion and (b) independent guidance carried out by the KUA. (2) Obstacles in implementing premarital guidance according to the Decree of the Director General of Islamic Guidance Number 379 of 2018 consist of two obstacle factors, namely: the organizer factor and the bride and groom factor.